"Hindrance" and "Love" Pay Attention to the Theme Poster Design of Alexithymia (Asian Journal of Social Science Studies, 2022)
In social life, people's emotional communication lies in communication. Loss of communication ability will make people's emotional indifference, and make more people suffer from the difficulties caused by alexithymia. Aexithymia is characterized by the inability to identify, distinguish, and express certain emotions of oneself or others. The emergence of this disease will affect people's lives. Therefore, through the design of the theme posters, more people can pay attention to alexithymia and call on people to increase emotional communication. So that people can live healthier lives in their social lives.